The rationality of belief & the plurality of faith : essays in honor of William P. Alston - Alston, William P.; Senor, Thomas D. (Thomas David), 1960- (Cornell University Press, 1995)
"A veritable who's who in the field of contemporary philosophy of religion here considers various issues in the epistemology of religious beliefs. The writings of William P. Alston, the leading figure in the revival of the Anglo-American philosophy of religion, provide the focus of these essays, all but two previously unpublished. Philosophers of religion, epistemologists, metaphysicians, and theologians will find in this volume some of the most important work available in the theory of knowledge and the epistemic status of religious belief." "Essays are arranged in three sections: Natural Theology and the Knowledge of God, The Epistemology of Religious Experience, and Religious Pluralism. Collectively they create a dialogue on some of today's urgent issues in religion, including religious diversity."--Jacket